The use of stability criteria for ìall in oneî parenteral nutrition solutions in paediatrics. Issue 2 (12th March 2012) - Ferrit, M.; Cancela, B.; Araque, P.; Alañon, A.M.; Ubago, R.; Torne, M.; Muñoz, L.; Vallecillo, P.; Salazar, M.; Calleja, M.A.
Abstract : Background: The use of 'all in one' parenteral nutrition solutions (PNS) is supposed to reduce the problem of the instability of lipid emulsions, caused by the addition of different nutrients to the mixture. However, it is necessary to review the concentrations in the final mixture. Purpose: The objective was for the pharmacist to evaluate 'all in one' paediatric PNS prescriptions against stability criteria. Materials and methods: A prospective study was performed (January-June 2011). The prescriptions of PNS in children younger than 1 year were reviewed. Later, an evaluation was made according to the 'all in one' PNS stability criteria developed by the Spanish Society of Hospital Pharmacy (SSHP). The requirements established for the maintenance of the stability are concentrations ≥5% glucose, ≥2.5% amino acids and ≥1.5% lipids. The pharmacist made the necessary adjustments according to the requirements of each patient and the SSHP criteria. Results: 50 paediatric patients received PNS. The average age of the patients was 1.76 months and an average weight of 3.97 kg. The average volume administered was 300 ml. The authors observed that 64.2% of the PNS prescribed achieved the requirements of stability. In 35.8% of the prescriptions The authors detected inadequate concentrations of nutrients, specifically, low concentrations of: glucose (0.2%), amino acids (1%), lipids (29.4%), glucose and lipids (0.2%), amino acids and lipids (3.8%) and glucose, amino acids and lipids (0.4%). The pharmacist made the necessary adjustments in the 30% of PNS prescriptions by changing the nutrient content and/or the volume. Conclusions: The 'all in one' PNS is the ideal form of administration in paediatrics. If the pharmacist evaluates and adjusts the composition of the nutrients according to the stability criteria, this will avoid mistakes in 35% of PNS prescriptions.